Effectiveness of Self-Compassion Therapy on Psychological Distress and Quality of Life of Psoriasis Skin Patients - Azam Arabi; jafar Hasani; mehdi Akbari; Mohammad Hatami; Mohammad Reza Sherbafchi Zadeh (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2021)
Aim and Background: Skin diseases, such as psoriasis, are associated with significant psychological and social disabilities. Therefore, the current research was done with the aim of examining the effectiveness of self-compassion Therapy on psychological distress and quality of the life of Psoriasis Skin Patients. Methods and Materials: This research is a semi-experimental with control group and follow-up which was observed for a month. The statistical population of the research includes all skin patients with psoriasis who went to skin treatment centers in Tehran between Dec and Feb in 2019. From this population, 40 people were selected by available sampling method and after matching were randomly assigned to experimental (20 people) and control (20 people) groups. The subjects of experimental group received seven sessions of self-compassion Therapy, however, the control group did not receive any training. The questionnaires of Kessler's Psychological Distress (2002) and Bref's Quality of Life (1996) were distributed before and after educational interventions as pretest, posttest and follow up study on all subjects. The findings of the research were analyzed with Variance with repeated measures and SPSS-20 software. Findings: The results of the analysis showed that the self-compassion Therapy was significantly effective in reducing psychological distress and increasing quality of life in Psoriasis Skin Patients (p <0.05). Conclusions: It seems that self-compassion Therapy can help improve psychological distress and quality of life of Psoriasis Skin Patients by increasing kindness to oneself and others and managing emotions.